2006
DOI: 10.1111/j.1600-0420.2006.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between Pascal dynamic contour tonometry, the TonoPen, and Goldmann applanation tonometry in patients with glaucoma

Abstract: ABSTRACT.Purpose: To compare intraocular pressure (IOP) measurements taken with Pascal dynamic contour tonometry (DCT), the TonoPen and the Goldmann applanation tonometry (GAT). The influence of central corneal thickness (CCT) on IOP measurements taken with Pascal DCT and the TonoPen was evaluated.Methods: One eye in each of 101 consecutive patients with primary open-angle glaucoma (POAG) underwent ultrasonic CCT measurement and IOP evaluation with GAT, Pascal DCT and the TonoPen in random order. The agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 39 publications
8
95
1
6
Order By: Relevance
“…This value appears greater than those reported previously, which varied between 0.94 and 2 mmHg. 11,12,16,17 The tendency of DCT to give higher IOP readings compared with GAT is in good agreement with the results of a recently published study, which demonstrated that the IOP measured by applanation tonometry was 1.2-2 mmHg lower than the IOP measured manometrically in human in vivo eyes. 18 The higher readings obtained with DCT may be expected, as DCT was calibrated against a manometrically controlled standard pressure rather than a GAT pressure reading.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This value appears greater than those reported previously, which varied between 0.94 and 2 mmHg. 11,12,16,17 The tendency of DCT to give higher IOP readings compared with GAT is in good agreement with the results of a recently published study, which demonstrated that the IOP measured by applanation tonometry was 1.2-2 mmHg lower than the IOP measured manometrically in human in vivo eyes. 18 The higher readings obtained with DCT may be expected, as DCT was calibrated against a manometrically controlled standard pressure rather than a GAT pressure reading.…”
Section: Discussionsupporting
confidence: 80%
“…As previously shown by Salvetat et al, 16 our study showed that neither DCT nor GAT IOP readings were correlated with age. Interestingly, Kotecha et al 26 found that GATÀDCT differences were positively associated with age.…”
Section: Discussionsupporting
confidence: 74%
“…35 However, its accuracy has been questioned in eyes with abnormal central corneal thickness and structural rigidity, and in those that have undergone corneal ablation with laser refractive surgery. 35 Goldmann applanation tonometry was calibrated for a CCT of 520µm, and it underestimates IOP in eyes with thin corneas and overestimates IOP in eyes with thick corneas, with several clinical implications. 35 The Pascal dynamic contour tonometer (DCT) is a novel device designed for IOP measurements assumed to be largely independent on CCT and corneal curvature.…”
Section: Intraocular Pressurementioning
confidence: 99%
“…35 Goldmann applanation tonometry was calibrated for a CCT of 520µm, and it underestimates IOP in eyes with thin corneas and overestimates IOP in eyes with thick corneas, with several clinical implications. 35 The Pascal dynamic contour tonometer (DCT) is a novel device designed for IOP measurements assumed to be largely independent on CCT and corneal curvature. 35 When Goldmann applanation tonometer was compared with the TonoPen and DCT, agreement with GAT measurements was higher for Pascal DCT than for TonoPen readings; however, Pascal DCT significantly overestimated IOP values compared with GAT.…”
Section: Intraocular Pressurementioning
confidence: 99%
See 1 more Smart Citation